Design and assessment of amblyopia, strabismus, and myopia treatment and vision training using virtual reality - Hoi Sze Chan; Yuk Ming Tang; Chi Wai Do; Horace Ho Yin Wong; Lily YL Chan; Suet To (Digital Health, 2023)
Background Virtual reality is a relatively new intervention that has the potential to be used in the treatment of eye and vision problems. This article reviews the use of virtual reality-related interventions in amblyopia, strabismus, and myopia research. Methods Sources covered in the review included 48 peer-reviewed research published between January 2000 and January 2023 from five electronic databases (ACM Digital Library, IEEE Xplore, PubMed, ScienceDirect and Web of Science). To prevent any missing relevant articles, the keywords, and terms used in the search included “VR”, “virtual reality”, “amblyopia”, “strabismus,” and “myopia”. Quality assessment and data extraction were performed independently by two authors to form a narrative synthesis to summarize findings from the included research. Results Total number of 48 references were reviewed. There were 31 studies published on amblyopia, 18 on strabismus, and 6 on myopia, with 7 studies overlapping amblyopia and strabismus. In terms of technology, smartphone-based virtual reality headset viewers were utilized more often in amblyopia research, but commercial standalone virtual reality headsets were used more frequently in myopia and strabismus-related research. The software and virtual environment were mostly developed based on vision therapy and dichoptic training paradigms. Conclusion It has been suggested that virtual reality technology offers a potentially effective tool for amblyopia, strabismus, and myopia studies. Nonetheless, a variety of factors, especially the virtual environment and systems employed in the data presented, must be explored before determining whether virtual reality can be effectively applied in clinical settings. This review is significant as the technology in virtual reality software and application design features have been investigated and considered for future reference.